THE USE OF FUEL IN THE GASEOUS STATE USED FOR CARS (Modern education and development, 2025)
This article explores the use of gaseous fuels in the automotive industry, focusing on their environmental, economic, and technical advantages. By analyzing the current literature on gaseous fuels such as compressed natural gas (CNG), liquefied petroleum gas (LPG), and hydrogen, the paper outlines the methods, results, and future prospects for integrating these fuels into the automotive sector. It also presents suggestions for further development and implementation.